Removal and exclusion of foreign nationals : issues and considerations - Gibson, Delia (Immigration in the 21st century: political, social and economic issues., 2015)
The ability to remove foreign nationals (aliens) who violate U.S. immigration law is central to the immigration enforcement system. Some lawful migrants violate the terms of their admittance, and some aliens enter the United States illegally, despite U.S. immigration laws and enforcement. This book provides an overview of removing foreign nationals from the United States. It discusses immigration policies and issues on health-related grounds for exclusion; terrorist grounds for exclusion and removal of aliens; and the consequences of criminal activity for immigrants.